CITED4 Protects Against Adverse Remodeling in Response to Physiological and Pathological Stress. Issue 5 (14th August 2020) - Lerchenmüller, Carolin; Rabolli, Charles P.; Yeri, Ashish; Kitchen, Robert; Salvador, Ane M.; Liu, Laura X.; Ziegler, Olivia; Danielson, Kirsty; Platt, Colin; Shah, Ravi; Damilano, Federico; Kundu, Piyusha; et al.
Abstract : Rationale: Cardiac CITED4 (CBP/p300-interacting transactivators with E [glutamic acid]/D [aspartic acid]-rich-carboxylterminal domain4) is induced by exercise and is sufficient to cause physiological hypertrophy and mitigate adverse ventricular remodeling after ischemic injury. However, the role of endogenous CITED4 in response to physiological or pathological stress is unknown. Objective: To investigate the role of CITED4 in murine models of exercise and pressure overload. Methods and Results: We generated cardiomyocyte-specific CITED4 knockout mice (C4KO) and subjected them to an intensive swim exercise protocol as well as transverse aortic constriction (TAC). Echocardiography, Western blotting, qPCR, immunohistochemistry, immunofluorescence, and transcriptional profiling for mRNA and miRNA (microRNA) expression were performed. Cellular crosstalk was investigated in vitro. CITED4 deletion in cardiomyocytes did not affect baseline cardiac size or function in young adult mice. C4KO mice developed modest cardiac dysfunction and dilation in response to exercise. After TAC, C4KOs developed severe heart failure with left ventricular dilation, impaired cardiomyocyte growth accompanied by reduced mTOR (mammalian target of rapamycin) activity and maladaptive cardiac remodeling with increased apoptosis, autophagy, and impaired mitochondrial signaling. Interstitial fibrosis was markedly increased in C4KO hearts after TAC. RNAseq revealed induction of a profibrotic miRNA network. miR30d was decreased in C4KO hearts after TAC and mediated crosstalk between cardiomyocytes and fibroblasts to modulate fibrosis. miR30d inhibition was sufficient to increase cardiac dysfunction and fibrosis after TAC. Conclusions: CITED4 protects against pathological cardiac remodeling by regulating mTOR activity and a network of miRNAs mediating cardiomyocyte to fibroblast crosstalk. Our findings highlight the importance of CITED4 in response to both physiological and pathological stimuli. Abstract : Supplemental Digital Content is available in the text.